Power Management in Microgrid: Analysis in Grid Connected and Islanded Mode of Operation - Niraj Kumar Choudhary; Soumya Ranjan Mohanty; Ravindra Kumar Singh (Institute of Advanced Engineering and Science, 2017)
This paper presents an investigation about the impact of integrating renewable energy based generation sources on the existing distribution system in terms of load sharing. The study of load sharing among various distributed generators (DGs) and utility grid has been performed for two cases: (a) when equivalent source based DG is connected and (b) when real PV/Fuel cell based DG is properly integrated to the distribution system. The real photovoltaic and fuel cell based DG do not behave as stiff current/voltage source due to disturbances happening either internally in system known as parametric uncertainties or due to external disturbances like weather conditions, load change etc. Further it has been observed with extensive analysis using simulation result, that even though all DGs are of equal capacity in their generation but when the load is either increased or decreased this doesn’t essentially guarantee that all DGs will equally share the active and reactive power demand.